Blink - the power of thinking without thinking - Gladwell, Malcolm (London: Back Bay/Little, Brown & Co., 2005)
INTUITION IS OFTEN PRESENTED AS THE OPPOSITE OF STRUCTURED ACHIEVEMENT. THERE ARE PEOPLE WHO INTUIT THE ANSWER TO A PROBLEM, AND THERE ARE THOSE WHO WORK IT OUT THE LONG AND HARD WAY. THIS DISTINCTION IS FALSE: INTUITIVE FACILITIES TURN OUT TO BE GIFTS THAT ARE DEVELOPED AND EDUCATED BY PRACTICE AND EXPERIENCE.
Keywords: Decision making; Intuition